Contribution of congenital malformations of the digestive system in the structure of mortality of newborns - G.S. Tchaikovska; A.Z. Gnateyko; A.A. Dvorakevich; R.V. Stenik (Bukovynian State Medical University, 2019)
The analysis of frequency of gastricduodenal congenital malformations in lethality structure was carried out among newborns which were cured last 5 years in regional children clinical hospital. This pathology occurres in every third lethality case among newborns with congenital malformation's with frequency q = 0,60 in boys from rural region. The availability of probable risk factors in pregnant women who gave birth children with gastric-duodenal congenital malformations was found out.